2022
DOI: 10.22541/au.165893766.64488370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interrogating 1000 Insect Genomes for NUMTs: A Risk Assessment for Species Scans

Abstract: The nuclear genomes of most animal species include segments of the mitogenome, but the count of these NUMTs varies greatly. This study examines the incidence of NUMTs derived from a 658 bp region of the cytochrome c oxidase I (COI) gene as a proxy for other coding regions of the mitochondrial genome. Analysis focuses on the most diverse group of terrestrial organisms, insects, because COI-based identification systems play a key role in clarifying their diversity, an essential antecedent to genome sequencing. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…NUMTs have been recognized as a critical issue in phylogenetics (Bensasson et al,, 2001), but they are particularly harmful to DNA barcoding and metabarcoding studies (Graham et al, 2021; Song et al, 2008; Sorenson & Quinn, 1998). Our results showed that even after strict data quality filtering (sequences with minimum coverage of less than 10, stop codons or InDels were removed), a high number of putative NUMTs may be detected (Hebert et al, 2022). Even considering that we obtained a comparatively large COI fragment (658 bp) has helped to decrease the number of NUMTs substantially (Hebert et al, 2022; Kaya & Çıplak, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…NUMTs have been recognized as a critical issue in phylogenetics (Bensasson et al,, 2001), but they are particularly harmful to DNA barcoding and metabarcoding studies (Graham et al, 2021; Song et al, 2008; Sorenson & Quinn, 1998). Our results showed that even after strict data quality filtering (sequences with minimum coverage of less than 10, stop codons or InDels were removed), a high number of putative NUMTs may be detected (Hebert et al, 2022). Even considering that we obtained a comparatively large COI fragment (658 bp) has helped to decrease the number of NUMTs substantially (Hebert et al, 2022; Kaya & Çıplak, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Our results showed that even after strict data quality filtering (sequences with minimum coverage of less than 10, stop codons or InDels were removed), a high number of putative NUMTs may be detected (Hebert et al, 2022). Even considering that we obtained a comparatively large COI fragment (658 bp) has helped to decrease the number of NUMTs substantially (Hebert et al, 2022; Kaya & Çıplak, 2018). The species in order Orthoptera are well known to have large nuclear genomes (Hanrahan & Johnston, 2011), and they are also reported to have an extremely high number of nuclear mitochondrial DNA copies (Kaya & Çıplak, 2018; Song et al, 2008, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations